Karakteristik Sosial Demografi dan Faktor Pendorong Peningkatan Kinerja Kader Posyandu - Megawati Simanjuntak (Lembaga Penelitian & Pengabdian pada Masyarakat (LPPM) Universitas Mikroskil, 2012)
Posyandu is one of the community participation approach in health sector that is managed by cadres, with the main problem arises is the declining number of visits of mothers of infants and toddlers. The aims of this research were to analyze the level of performance of posyandu cadres, and to analyze the factors that influence performance. Research conducted in Ciherang village with 30 samples that was selected using random sampling. Most of the cadres including productive age, junior secondary education, medium families size, and has been married to a third have children under five. The average of job length was 9 years old, had attended training related to posyandu, a cadres motivation is the desire to help the community. Average cadres incentives was Rp20,000 per person per month with the support of family and community leaders. The result showed that most of cadres’ performance can be categorized high. The higher the incentives and the more participation of cadres in training at least once influenced significantly for the improving of cadres’ performance.